Newly Developed Thermal Load Profile for Enhancement in Hot Water System - Munirah, Nawi; Norazlianie, Sazali; S. A., Che Ghani; Kettner, Maurice (Akademia Baru Publishing (M) Sdn Bhd, 2021)
In recent years with the advancement of technologies, the demand of a reliable and flexible hot water system has increased tremendously. A reliable system includes several critical points which are the degree of safety that a system can offer, the conservation of the energy used and the issue of cost saving. While a flexible system must provide the flexibility in the control of the output from a system desired by the consumers itself. This paper reported on newly developed system for hot water that will greatly benefit consumer. It focuses on building an extension of the cyber physical system in the existing system with purposes of implementing a thermal load profile for consumer who use the hot water system in their daily life. The implementation of the thermal load profile to the system is significant especially in conserving the energy used in the system simultaneously saving any related cost to operate the system. Based on the implemented thermal load profile, the system works in maintaining an output of thermal energy from the hot water supplied to the consumer at a certain value. In addition, it also allows flexibility in controlling the desired temperature by consumers. This new system is simulated in a test bench in the form of laboratory setup. The system uses a control loop feedback mechanism, which means that it will continuously regulate the temperature and mass flow rate of the flowed water in the pipeline for the consumer hot water simulation based on the calculated difference of the actual supplied values and the set values. With the use of standard devices and actuators to drive the system, a robust system can be realized.